Cytoreduction and Hyperthermic Intraperitoneal Chemotherapy for Pseudomyxoma Peritonei of Appendiceal Origin: A Single Center Experience - Santullo, Francesco; Pacelli, Fabio; Abatini, Carlo; Attalla El Halabieh, Miriam; Fortunato, Giusy; Lodoli, Claudio; Giovinazzo, Francesco; Rotolo, Stefano; Di Giorgio, Andrea (Frontiers in Surgery, 2021)
Background: Pseudomyxoma peritonei (PMP) originating from appendiceal mucinous neoplasm is a rare peritoneal malignancy characterized by the progressive intraperitoneal accumulation of mucus leading to death if left untreated. In recent years, cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) offered increased survival rates. This study aims to identify the clinical, pathological, and surgical features influencing safety and survival outcomes of patients undergoing CRS and HIPEC for PMP of appendiceal origin. Methods: A retrospective analysis of all patients undergoing CRS and HIPEC for PMP of appendiceal origin from January 2015 to May 2019 was conducted at our institution. Results: Study population included 50 patients (74% female, 26% male). The median age at CRS was 60 (38-84). The median peritoneal cancer index (PCI) was 17. Complete cytoreductive surgery (CC 0-1) was achieved in 47 patients (94%). HIPEC chemotherapeutic regimen was based on oxaliplatin for 13 (28%) patients and mitomycin for 34 (72%) patients. We experienced a total of 19 (38%) postoperative complications, of which 14 (74%) of grade I-II and 5 (26%) of grade III-IV, according to the Clavien-Dindo classification. The median follow-up period was 27 months (12 – 107) from the date of cytoreductive surgery. The mean survival rate was 100 months, with a 5-year OS of 91%. The mean progression-free survival rate was 77 months (0 – 107), with a 5-year PFS of 63%. Multivariate analysis identified adenocarcinoma histotype and incomplete cytoreduction to significantly worsen progression-free survival, while incomplete cytoreduction was the only independent predictor of poorer overall survival. Conclusion: Complete cytoreduction and appendiceal neoplasm histotype play a crucial role in the survival of patients affected by PMP of appendiceal origin. The rates of morbidity associated with CRS and HIPEC for PMP are acceptable.